Tough Choices: Exploring Decision-Making for Pregnancy Intentions and Prevention Among Girls in the Justice System. (October 2019) - Saleeby, Erin; O'Donnell, Betsy; Jackson, Ashaki M.; Muñiz, Cecilia; Chung, Paul J.; Sufrin, Carolyn
Despite California's declining teen pregnancy rate, teens in the juvenile justice system have higher rates than their nonincarcerated counterparts. This study explored domains that may shape decision-making for pregnancy prevention in this group. Twenty purposively selected female teens with a recent incarceration participated in hour-long semistructured interviews about their future plans, social networks, access to reproductive health services, and sexual behavior. Transcripts revealed that, contrary to literature, desire for unconditional love and lack of access to family planning services did not mediate decision-making. Lack of future planning, poor social support, and limited social mobility shaped youths' decisions to use contraceptives. Understanding this group's social location and the domains that inform decision-making for pregnancy intentions and prevention provides clues to help programs predict and serve this population's needs.